Rebeldia em cena: a juventude transviada no cinema hollywoodiano nas décadas de 1950 e 1960 - Viteck, Cristiano Marlon (2009)
The concept of teenager, which during the first half of the 20th century was being discussed in the United States, received importance since 1950, when it was definitely noticed that the adolescence constituted a huge cultural and social phenomenon on the American society. A noticeable characteristic from that generation was the contest of some determined social values. This phenomenon got much bigger during the 1960 s with the counter culture, that took the rebel youth as the main character of its manifestations. The cinema produced by Hollywood also influenced and at the same tame influenced these manifestations. Trough a process called juvenilization of the cinema, the cinematography industry of the United States started to produce a lot of work that were bringing a diversity of representations of the issues related to the youth theme during the 1950 s, and the rebel characteristic of a significant part of those young people was used as an argument for a lot of these films, the same happened during the 1960 s during the XXX. Trough the analyses of the movies The Wild One (1954), Rebel Without a Cause (1955) and Easy Rider (1969), we intend to comprehend the social imaginary and the behavior of some determined youth groups of the 1950 s and 1960 s, as well as highlight important elements of the American society from the times they were being contested.